Micropropagation of Mini Orchid Hybrid Phalaenopsis “Sogo Vivien” - Exsyupransia Mursyanti; Aziz Purwantoro; Sukarti Moeljopawiro; Endang Semiarti (Universitas Gadjah Mada, 2016)
Phalaenopsis “Sogo Vivien” is an orchid hybrid with mini size plant body, and exhibits numerous beautiful pink flowers, that is ideal as ornamental pot plant. Some plants of this orchid exhibit variegated leaves that improve the beauty of the plant, not only because of the flower but also as attracted leaves. This orchid has high economical value, but mass propagation of this orchid has not established yet. An effective method to propagate both the normal and variegated plants is worth to be generated. The objective of this research was to produce a large number of P. “Sogo Vivien” plants, including the variegated plants. The method used seeds from self pollinating variegated plant, and flower stalk nodes. The seeds were sown on three various medium: VW, NP and MS, and flower stalk nodes were planted on VW + BA 10 mg l-1 + active carbon. The results showed that the best medium for in vitro culture of P. “Sogo Vivien” was NP medium, in which all seeds could grew into plantlets. Most plantlets emerged from the seeds were non variegated, only one plantlet out of 1344 seeds was variegated (0.007%). Although all emerged plantlets from flower stalk exhibited variegated leaves. Particularly, the plantlets arised from the second and third basal nodes of flower stalk showed the highest growth rate than that from the other nodes. Histological analysis showed that at 11-13 days after shoot segment plantation on NP medium, the shape of apical cells in the nodes was changed, then followed by the change of cell shape in the basal part of the nodes, produced bipolar pattern, then gradually developed into shoot. These results suggest that mass propagation could be achieved using seed culture, but to get the variegated phenotypes, the second and third nodes of flower stalk from variegated plant were the best explants to be used.